Rumi and Shams’ Silent Rebellion - Vaziri, Mostafa. author. aut Link
XVII, 244 p.
Keywords: This book offers a paradigm shift and fresh interpretation of Rumi's message. After being disentangled from the anachronistic connection with the Mevlevi order of Islamic Sufism, Rumi is instead placed in the world of philosophy.